Determinants of Audit Report Quality: Enhancing Fraud Detection through Auditor Independence and Internal Control Systems at Public Accounting Firm Kanaka Puradiredja Suhartono - Syifa Ragustia Prabowo; Yeni Elfiza Abbas; Nur Asmilia; Aulia Rahmawati; Nanda Fathiya Rizky (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
Fraudulent Financial Reporting is the intentional misstatement of amounts and disclosures with the intention of deceiving users of financial statements by disclosing higher amounts than true (overstates) of assets or income, or when the company reports lower amounts than true (understates) of liabilities and expenses. This study examines the effects of fraud auditing, auditor independence, and internal control systems on audit report quality at Kanaka Puradiredja Suhartono Public Accounting Firm. Using a quantitative causal comparative design, data were collected from 61 auditors via validated questionnaires. Hypotheses were tested through partial t-tests, simultaneous F-tests, and multiple regression analysis processed with SPSS Version 30. Results show that fraud auditing and internal control systems significantly improve audit report quality, while auditor independence has no significant partial effect. The findings highlight the importance of enhancing fraud detection capabilities and internal controls to elevate audit quality. This study provides empirical evidence to guide auditors and regulators in strengthening audit standards and control systems in Indonesian public accounting firms.